On a counterexample of Garofalo - Lin for a unique continuation of Schrödinger equation. (1991) - Lee, Will Y.
Abstract : Garofalo and Lin have given a counterexample for which unique continuation fails for the Schrödinger equation − Δ u + c | x | 2 + ϵ u = 0,   ϵ > 0 . Their counterexample consists of a Bessel function of the third kind K v ( | x | ) with the restriction that v cannot be an integer. In this note we have removed the restriction.